2017
DOI: 10.11114/bms.v3i2.2408
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Entrepreneurial Orientation and Performance; Evidence from Turkish SMEs

Abstract: This research aims to find the factors linked to Entrepreneurial orientation and corporate entrepreneurship that effect export and sales growth performance of SMEs. Thereby a model was developed to reveal the relationship between these factors. The questionnaire had parts such as general information about firm and owner/manager, entrepreneurial orientation, corporate entrepreneurship and growth in sales revenue and exportation rate over the most recent 3 year period of the SMEs. The measurements have been gath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Starting from the courage to start a busi-ness, actively seeking information, dare to take risks, flexible and anticipatory (Hartanty and Ratnawati, 2013). The results of this study reinforce the Weerawardena and Coote (2001) and Platin and Ergun (2017), concluded that entrepreneurial orientation influences competitive advantage.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Starting from the courage to start a busi-ness, actively seeking information, dare to take risks, flexible and anticipatory (Hartanty and Ratnawati, 2013). The results of this study reinforce the Weerawardena and Coote (2001) and Platin and Ergun (2017), concluded that entrepreneurial orientation influences competitive advantage.…”
Section: Discussionsupporting
confidence: 86%
“…Entrepreneurial orientation is formed through four dimensions, namely innovative, proactive, risk-taking, and aggressiveness in competition (Weerawardena and Coote, 2001). Research conducted by Platin and Ergun (2017) proves entrepreneurial orientation and competitive advantage have a positive and significant relationship.…”
mentioning
confidence: 99%
“…A literature evidence by Fable and Larwood (1995) further enhanced it whereby their research findings indicated that entrepreneurs score high on risk taking behaviour in comparison to non-entrepreneurs. Therefore, a claim that there is relationship between reward and reinforcement system and also risk-taking behaviour fall in line with assertion by Platin and Ergun (2017) who argues that an existence of appropriate reward system encourages a risk-taking behaviour which in turn creates a tendency to behave more entrepreneurially.…”
Section: Risk-takingsupporting
confidence: 71%
“…The said relationship can be intervened and mediated by the variable of OXEL. Platin and Ergun (2017) pointed out that only 15 studies had examined the relationship between ENTO and OP using a mediating variable, and that most of the findings had indicated at least a partial mediation effect. This means that the use of a mediating variable could act as a mechanism for explaining the correlation between ENTO and OP.…”
Section: Introductionmentioning
confidence: 99%